2019
DOI: 10.1002/advs.201902538
|View full text |Cite
|
Sign up to set email alerts
|

Local Electric‐Field‐Driven Fast Li Diffusion Kinetics at the Piezoelectric LiTaO3 Modified Li‐Rich Cathode–Electrolyte Interphase

Abstract: HEVs (PHEVs), besides the traditional applications in portable devices. To build the next generation LIBs with higher performances, high energy density materials are urgently pursued worldwide. [1][2][3] Lithium-rich (Li-rich) materials, with the specific capacity over 260 mAh g −1 and energy density up to ≈1000 Wh kg −1 , [4] have attracted great interest in the past decades. It is reported that Li-rich materials are composed of two phases of Li 2 MnO 3 (C 2/m ) and LiMO 2 (R m 3 ) (M = Ni, Co, Mn, etc.). [5]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 70 publications
2
89
0
Order By: Relevance
“…For the BTO modified samples, the increased rate capability is attributed to the generated built-in electric field pointing to the inner direction of the cathode material will act in promoting the diffusion of lithium-ions among the nickel-rich cathode, BTO nanodots, and the electrolyte phase interface, especially during the discharging process. [26,27] Figure S4 shows the comparison of the cycle performance among pristine NCM622 and various BTO contents modified NCM622 at C. The 0.5 wt.% BTO sample delivers 171 mAh g À 1 discharge capacity and the capacity retention is as high as 89 % after 100 cycles, and 0.25 %-NCM622@BTO has a discharge capacity of 163 mAh g À 1 (capacity retention rate of 88 %), which is better than 162 mAh g À 1 and 86 % capacity retention of pristine NCM622. For 1 %-NCM622@BTO, an excessively thick coating layer is formed on the surface of NCM622, which hinders the diffusion of lithium-ions and results in a substantial decrease with a discharge specific capacity of 147 mAh g À 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the BTO modified samples, the increased rate capability is attributed to the generated built-in electric field pointing to the inner direction of the cathode material will act in promoting the diffusion of lithium-ions among the nickel-rich cathode, BTO nanodots, and the electrolyte phase interface, especially during the discharging process. [26,27] Figure S4 shows the comparison of the cycle performance among pristine NCM622 and various BTO contents modified NCM622 at C. The 0.5 wt.% BTO sample delivers 171 mAh g À 1 discharge capacity and the capacity retention is as high as 89 % after 100 cycles, and 0.25 %-NCM622@BTO has a discharge capacity of 163 mAh g À 1 (capacity retention rate of 88 %), which is better than 162 mAh g À 1 and 86 % capacity retention of pristine NCM622. For 1 %-NCM622@BTO, an excessively thick coating layer is formed on the surface of NCM622, which hinders the diffusion of lithium-ions and results in a substantial decrease with a discharge specific capacity of 147 mAh g À 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[26] Si et al have constructed a piezoelectric LiTaO 3 coating layer between Li-rich cathode and the electrolyte interface, which can not only be used as an "initiative" accelerator to promote Li + diffusion kinetics, but also reinforces the Li-rich cathode structure. [27] Hence, BaTiO 3 (BTO) material combing the physical characteristics of piezoelectricity and ferroelectricity is regarded as an alternative material for the modification of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…[57d] Spectroscopic studies clearly identified decomposition of alkyl carbonates and LiPF 6 on LMLO electrodes and formation of polymeric decomposition products. [77,78] In general, all of the above-described undesirable surface reactions can be significantly inhibited by coating as a pretreatment or by in situ surface modification using electrolyte solutions which contain functional additives. [77] For example, Si et al prepared LiTaO 3 -coated LMLO with stabilized electrode-electrolyte solution interface by surface films that enable fast interfacial Li ion transport.…”
Section: Surface Reactions Under High Potentialsmentioning
confidence: 99%
“…[77] For example, Si et al prepared LiTaO 3 -coated LMLO with stabilized electrode-electrolyte solution interface by surface films that enable fast interfacial Li ion transport. [78] Xiao et al [82] and Nayak et al [79] used lithium bis(oxalato)borate (LiBOB) as an effective additive in solutions that form protecting surface films. Schematic mechanisms for the protective effect of surface films are shown in Figure 3b.…”
Section: Surface Reactions Under High Potentialsmentioning
confidence: 99%
“…This can be attributed to the high surface area of nanofibers which promotes enhanced interfacial electron transfer facilitated by strong local electric field gradient [49,50]. However, R ct gradually increased upon tyrosinase immobilization on the nanofibers (C/α-MnO 2 /tyrosinase); which can be attributed to the insulating nature of the enzyme thereby passivating the electrode surface [24].…”
Section: Tyrosine Sensing Performance Of Smart Band-aidmentioning
confidence: 99%